2010
DOI: 10.1007/s12394-010-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Viktor Mayer-Schönberger, Delete: the virtue of forgetting in the digital age

Abstract: Much ink has been spilt theorising and documenting the transformation of our societies from an industrial age towards an information age (Webster 2002), network society (Castells 2001), or knowledge society (Mansell and Wehn 1998). Central to these visions is the importance and relatively free flow of massive amounts of information based upon new information and communication technologies. Indeed, a large part of the world is experiencing an information explosion with significant institutional and social impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Certain cloud services (e.g., NaaS, CaaS) can fall directly into the regulated sphere of telecommunications regarding networks and services. OTT cloud services (e.g., SaaS, PaaS) provided through public access to the Internet (based on the network-neutral principle) are not treated as separate telecommunication services [74].…”
Section: Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…Certain cloud services (e.g., NaaS, CaaS) can fall directly into the regulated sphere of telecommunications regarding networks and services. OTT cloud services (e.g., SaaS, PaaS) provided through public access to the Internet (based on the network-neutral principle) are not treated as separate telecommunication services [74].…”
Section: Securitymentioning
confidence: 99%
“…After studying most research articles, we convexed the identified challenges of the smart city over CC in Table 2. Table 2 illustrates the identified threats and challenges to the CC domain in the smart city networks and the compromised security attributes related to the CIA triad [74]. Furthermore, the different authors have resolved many issues in their article work; however, they have not achieved some of the most important aspects.…”
Section: Attacks Threats and Vulnerabilities In Cc-based Smart City N...mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on this subject approaches this new law and its ethical foundation from managerial, legal, and societal perspectives [ 1 , 2 , 9 , 15 , 17 , 18 , 31 , 33 , 52 , 67 , 69 , 70 ]. Regardless of the disciplinary perspective from which the subject is approached, it is stressed the new paradigm created by technology—eradicating one of human memory’s functions—the ability to forget [ 14 , 46 , 71 ]. In general, the “right to be forgotten” is valuable for dealing with outdated, useless or decontextualised information [ 35 , 49 ].…”
Section: The Right To Be Forgotten and Trans Identity Informationmentioning
confidence: 99%